Cultural Change: The How and the Why. (November 2017) - Varnum, Michael E. W.; Grossmann, Igor
More than half a century of cross-cultural research has demonstrated group-level differences in psychological and behavioral phenomena, from values to attention to neural responses. However, cultures are not static, with several specific changes documented for cultural products, practices, and values. How and why do societies change? Here we juxtapose theory and insights from cultural evolution and social ecology. Evolutionary approaches enable an understanding of the how of cultural change, suggesting transmission mechanisms by which the contents of culture may change. Ecological approaches provide insights into the why of cultural change: They identify specific environmental pressures, which evoke shifts in psychology and thereby enable greater precision in predictions of specific cultural changes based on changes in ecological conditions. Complementary insights from the ecological and cultural evolutionary approaches can jointly clarify the process by which cultures change. We end by discussing the relevance of cultural change research for the contemporary societal shifts and by highlighting several critical challenges and future directions for the emerging field of cross-temporal research on culture and psychology.